2019
DOI: 10.1002/jia2.25258
|View full text |Cite
|
Sign up to set email alerts
|

Routine versus Targeted Viral Load Strategy among Patients Starting Antiretroviral in Hanoi, Vietnam

Abstract: Introduction HIV viral load (VL) testing is recommended by the WHO as the preferred method for monitoring patients on antiretroviral therapy (ART). However, evidence that routine VL (RVL) monitoring improves clinical outcomes is lacking. Methods We conducted a prospective, randomized controlled trial of RVL monitoring every six months versus a targeted VL (TVL) strategy (routine CD4 plus VL testing if clinical or immunological failure) in patients starting ART between April 2011 and April 2014 at Bach Mai Hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…However, we speculate that this may have been due to clinicians requesting earlier VL testing based on the need to know, for example in pregnant women, or later VL testing based on patient clinical status. While previous studies have shown that routine VL monitoring results in earlier detection of virologic failure and earlier switching to second-line ART [ 21 , 22 ], a recent study in Vietnam showed no difference in rates of failure or death between routine and targeted VL testing [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, we speculate that this may have been due to clinicians requesting earlier VL testing based on the need to know, for example in pregnant women, or later VL testing based on patient clinical status. While previous studies have shown that routine VL monitoring results in earlier detection of virologic failure and earlier switching to second-line ART [ 21 , 22 ], a recent study in Vietnam showed no difference in rates of failure or death between routine and targeted VL testing [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 Department of Statistics, Faculty of Science, Kasetsart University, Bangkok, Thailand; 2 HIV-NAT, Thai Red Cross AIDS Research Centre, Bangkok, Thailand; 3 The Kirby Institute, UNSW, Sydney, New South Wales, Australia; 4 Sydney School of Public Health, The University of Sydney, Sydney, New South Wales, Australia; 5 BJ Government Medical College and Sassoon General Hospital, Pune, India; 6 Queen Elizabeth Hospital, Kowloon, Hong Kong SAR; 7 National Hospital for Tropical Diseases, Hanoi, Vietnam; 8 Chiang Mai University -Research Institute for Health Sciences, Chiang Mai, Thailand; 9 Division of Infectious Diseases and Tropical Medicine, Department of Medicine, Faculty of Medicine, Chiang Mai University, Chiang Mai, Thailand; 10 National Center for HIV/AIDS, Dermatology & STDs, Phnom Penh, Cambodia; 11 Taipei Veterans General Hospital, Taipei, Taiwan; 12 Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, Thailand; 13 Chiangrai Prachanukroh Hospital, Chiang Rai, Thailand; 14 Beijing Ditan Hospital, Capital Medical University, Beijing, China; 15 Faculty of Medicine, Universitas Indonesia -Dr. Cipto Mangunkusumo General Hospital, Jakarta, Indonesia; 16 Chennai Antiviral Research and Treatment Clinical Research Site (CART CRS), VHS-Infectious Diseases Medical Centre, VHS, Chennai, India; 17 Institute of Infectious Diseases, Pune, India; 18 University Malaya Medical Centre, Kuala Lumpur, Malaysia; 19 Faculty of Medicine, Udayana University & Sanglah Hospital, Bali, Indonesia; 20 National Center for Global Health and Medicine, Tokyo, Japan; 21 Research Institute for Tropical Medicine, Muntinlupa City, Philippines; 22 Division of Infectious Diseases, Department of Internal Medicine, Yonsei University College of Medicine, Seoul, South Korea; 23 Tan Tock Seng Hospital, Singapore; 24 Bach Mai Hospital, Hanoi, Vietnam; 25 Hospital Sungai Buloh, Sungai Buloh, Malaysia; 26 TREAT Asia, amfAR -The Foundation for AIDS Research, Bangkok, Thailand…”
Section: A U T H O R S ' a F F I L I At I O N Smentioning
confidence: 99%
“…However, previous studies report that PLHIV from sites with routine VL testing switched to second-line ART after virologic failure was confirmed [6][7][8][9]. Studies from Asia indicate that routing VL testing can improve clinical outcomes [6,9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among patients enrolled in a randomized controlled trial who initiated ART between April 2011 and 2014 at a large HIV clinic in Hanoi, Vietnam, the median CD4 cell count at enrollment in HIV care was 130 cells/mL, and 35.5% (230/647) of participants had AIDS-defining OIs. 4 The high proportion of patients with advanced disease at the time of testing, delayed linkage to care, and late ART initiation all contribute to suboptimal clinical outcomes-lower retention rates, high loss to follow-up (LTFU), death, and OIs. 5 Cryptococcal disease is common among patients with advanced HIV and is an independent predictor of cryptococcal meningitis (CM) and death in HIV-infected individuals with advanced disease.…”
Section: Introductionmentioning
confidence: 99%